Audit Dan Peluang Penghematan Energi Listrik CV Tirta Windu Agung 3 Probolinggo - Duanaputri, Rohmanita; Muhammad Fahmi Hakim; Ahmad Jamaruddin; Tresna Umar Syamsuri (Elposys: Jurnal Sistem Kelistrikan, 2024)
The use of electrical energy in the building and industrial sectors is very important, especially the use and allocation of funds spent is quite large. So it is necessary to use energy as efficiently as possible. So there is a need for an energy audit to determine the level of electrical energy consumption used, where the results will be compared with predetermined standards. This research was carried out at CV Tirta Windu Agung 3 using a PM5100 and lux meter. From initial audit calculations, the IKE value was found to be 13.42 kWh/m2/year. This IKE value is the total of the buildings and ponds. The IKE value still includes very efficient criteria. Based on the results of detailed audit calculations, the value obtained before improvement was 2.23 kWh/m2/year. The IKE value still includes the criteria for being very efficient or meeting standards. After improvements it became 1.65 kWh/m2/year. Energy saving opportunities are available in indoor and outdoor lighting systems by replacing CFL (compact fluorescent lamp) lamps with Philips LED lamps. Based on calculations, the savings in electrical energy costs are IDR 41,736/day, resulting in savings of IDR 15,233,640/year. Based on the Isc/IL calculation above, it can be seen that the Isc/IL value is 165.4. According to the IEEE 519-2014 standard, the ISC IL value in the range >1000 has a permissible THDi value limit of 15%. The nominal voltage used is 0.4 kV, so the permitted THDv is 8%. Based on table 3.9 THDv and THDi under standard conditions.